The relationship between traumatic events and quality of sleep in older adults in rural South Africa - Dzimbanhete, Tsitsi Cherry (University of the Witwatersrand, Johannesburg, 2024)
Introduction: A number of factors are associated with the quality of sleep, a broad measure that includes sleep duration and disturbance. There are many factors associated with quality of sleep including communicable and non-communicable diseases and life course traumatic events (TE). Older adults who have experienced life course TE and the onset of comorbidities may be at risk of fluctuations in their quality of sleep. However, there are limited data on the African continent examining these relationships. Therefore, this study aimed to bridge the aforementioned gap and 1. examine the prevalence of traumatic events (TE), 2. examined the prevalence of poor quality of sleep in adults in the Health and Aging in Africa: a longitudinal study (HAALSI) cohort 3. examine the relationship between the TEs and quality of sleep in the HAALSI cohort in the Mpumalanga Province of South Africa. Methods: A cross sectional analysis using data from the second of four waves of the HAALSI cohort was undertaken. The second wave which recruited 4176 participants was conducted between 2018 and 2019. Measures include the English Longitudinal Study of Aging life history data to estimate prevalence of TE, brief version of Pittsburgh Sleep Quality Index (B-PSQI) to estimate the prevalence of poor sleep quality and the relationship between TE and poor sleep quality. Descriptive analysis, bivariate and multivariate analysis of the data was conducted in Stata 17. Results: The mean age of the participants was 65 years (SD=13). The majority of the sample were of South African origin (70%). With regard to education status, less than half (43%) had not completed a formal education (i.e., primary school). Poor quality of sleep was reported by 27% of the participants. With regards to TEs 66% of the sample reported caregiving trauma, 58% accident and disaster TEs, 30% childhood trauma, 15% war related TEs and 22% community violence. The multivariate analysis suggested that participants with history of exposure to childhood TEs and war related TEs had higher risk of poor sleep quality (OR 1.5 (CI1.2-1.8)) and (OR 1.5(CI 1.2-2.0)) respectively. The other variables associated with higher risk of poor sleep quality were being married (OR=1.2 (CI 1.0-1.4)) history of smoking (OR=1.6 (CI 1.2-3.1)), mild to moderate (OR=1.7 (CI 1.3-2.1)) and major depression symptoms (OR=2.1 (CI 1.8- 2.7)), being obese (OR =1.3 (CI 1.0-1.6)) and being HIV negative (OR= 1.4 (1.0-1.6)). Conclusion: Exposure to war related and childhood TEs were found to be associated with poor sleep quality in the older adults in rural South Africa. While a cross-sectional analysis is valuable, an examination of the full cohort of the trauma at baseline and quality of sleep would inform trauma focused interventions that seek to improve quality of sleep in older adults
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Epidemiology and Biostatistics to the Faculty of Health Sciences, School of Public Health, University of Witwatersrand, 2024
Keywords: Traumatic events; Quality of sleep; Older adultsI; Rural South Africa; HAALS; UCTD; SDG-3: Good health and well-being